(untitled) (International relations and international law Journal, 2020)
Iranian-Russian relations have a distinct strategic character, but they have not yet reached the level of strategic alliance, and the two parties in the Middle East, Central Asia and the Caucasus are more than they are different. The main organizer of these relations is temporary interests and common challenges, particularly the Western and American challenge. Therefore, there is always a common concern that both countries are likely to converge with the West at the expense of the other. “The study is important in analyzing the nature of relations between Russia and Iran. Both countries have strategic interests in an area of geo-strategic importance both at regional and international levels. The importance of these strategic relations goes beyond regional relations to the extent of the alliance, which makes the two countries on the road to the formation of a global axis, which gives great importance to understanding the nature and level of the relationship between the two countries. This study aims to study the development of Russian- Iranian relations and the nature of the factors influencing these relations in the period. The problem of the research is to try to analyze the nature of the Russian-Iranian relations and the controversy it raised over the dimensions of this relationship and its level and in view of the acquisition of this relationship of strategic importance at the international level. The relations between the two countries and areas of cooperation raised many questions to be addressed in this research. The main outcome of the study was that the two sides agree that the Arab Spring has begun to produce “radical Islamists.” Moscow does not favor a Middle East with al-Qaeda in its tracks, and Tehran does not favor radical Salafi control. Key words: Geopolitics, regional cooperation, internal cooperation, diplomacy, foreign policy initiatives, the main actors.